Foundations of intelligent systems 20th International Symposium, ISMIS 2012, Macau, China, December 4-7, 2012, proceedings - International Symposium on Methodologies for Intelligent Systems (Lecture notes in artificial intelligence, 2012)
This book constitutes the proceedings of the 20th International Symposium on Methodologies for Intelligent Systems, ISMIS 2012, held in Macau, China, in December 2012. The 42 regular papers and 11 short papers presented were carefully reviewed and selected from 88 submissions. They are organized in topical sections named: knowledge discovery and data mining; intelligent information systems; text mining and language processing; knowledge representation and integration; music information retrieval; recommender systems; technology intelligence and applications; product configuration; human factors in information retrieval; social recommender systems; and warehousing and OLAPing complex, spatial and spatio-temporal data. Knowledge discovery and data mining -- Intelligent information systems -- Text mining and language processing -- Knowledge representation and integration -- Music information retrieval -- Recommender systems -- Technology intelligence and applications -- Product configuration -- Human factors in information retrieval -- Social recommender systems -- Rehousing and OLAPing complex, spatial and spatio-temporal data.